Microstructure and property evolutions of titanium/nano-hydroxyapatite composites in-situ prepared by selective laser melting. (July 2017) - Han, Changjun; Wang, Qian; Song, Bo; Li, Wei; Wei, Qingsong; Wen, Shifeng; Liu, Jie; Shi, Yusheng
Abstract: Titanium (Ti)-hydroxyapatite (HA) composites have the potential for orthopedic applications due to their favorable mechanical properties, excellent biocompatibility and bioactivity. In this work, the pure Ti and nano-scale HA (Ti-nHA) composites were in-situ prepared by selective laser melting (SLM) for the first time. The phase, microstructure, surface characteristic and mechanical properties of the SLM-processed Ti-nHA composites were studied by X-ray diffraction, transmission electron microscope, atomic force microscope and tensile tests, respectively. Results show that SLM is a suitable method for fabricating the Ti-nHA composites with refined microstructure, low modulus and high strength. A novel microstructure evolution can be illustrated as: Relatively long lath-shaped grains of pure Ti evolved into short acicular-shaped and quasi-continuous circle-shaped grains with the varying contents of nHA. The elastic modulus of the Ti-nHA composites is 3.7% higher than that of pure Ti due to the effect of grain refinement. With the addition of 2% nHA, the ultimate tensile strength significantly reduces to 289 MPa but still meets the application requirement of bone implants. The Ti-nHA composites exhibit a remarkable improvement of microhardness from 336.2 to 600.8 HV and nanohardness from 5.6 to 8.3 GPa, compared to those of pure Ti. Moreover, the microstructure and property evolution mechanisms of the composites with the addition of HA were discussed and analyzed. It provides some new knowledge to the design and fabrication of biomedical material composites for bone implant applications. Graphical abstract: Highlights: Pure Ti and nano HA composites were in-situ prepared by selective laser melting. Microstructure evolution of composites with varying nHA contents was revealed. Surface topography evolution of composites in different nHA addition was illustrated. The nHA addition improves the modulus and hardness of Ti while reduces the strength.